Determinan Pinjaman Kebijakan Daerah Studi Kasus di Kabupaten Kota Provinsi Jawa Timur - Taufik Kurrohman (Jurnal Akuntansi dan Bisnis, 2009)
This paper identified the determinant of municipal debt. The factors of determinant municipal debt such as: GDP per-capita, economic growth, PAD, DAU, capital expenditure, surplus/deficit, and political faktor. The method was multiple regression with 38 objects. The result was all independent variable (GDP per-capita, economic growth, PAD, DAU, capital expenditure, surplus/deficit, and political faktor) influence the dependent variable (municipal debt) it means all hypothesis accepted.